Prevalence of white coat hypertension amongst pregnant women admitted with high BP recordings in ante-natal clinic - Sood, Sandeep; Ashta, Kuldeep Kumar; Anne, Sirisha; Kumar, Ravi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: White coat hypertension (WCH) is a common and well recognized phenomenon with significant prevalence amongst all age groups. This is also quite prevalent in the pregnant women with an intermediate long term prognosis between hypertensive and normo-tensive individuals. It is important to assess the true prevalence WCH in pregnant women and to prevent unnecessary medications to them during pregnancy but at the same time to keep a timely follow up and a watchful eye on these patients to identify complications at the earliest. Study was conducted at a peripheral secondary level hospital with a small obstetrics and gynecology OPD and ward. 54 patients were diagnosed to be hypertensive in Antenatal Clinic. Methods: All pregnant women who presented to the ANC were screened for hypertension. Those who were diagnosed to be hypertensive in antenatal clinic and these patients were then admitted for Ambulatory Blood Pressure Monitoring (ABPM) for 24 hours. Results: The ABPM tracings were checked and tabulated to arrive at the final diagnosis after 24 hrs. The prevalence of ‘WCH’ in this study was 48.15% as 26/54 patients were found to have their average BP < 140/90 mmHg after measurement by ABPM over 24 hours so they were diagnosed as ‘White Coat Hypertension’ patients. Conclusions: Many women who come to ANC in the early pregnancy are diagnosed to have hypertension. WCH is a well known phenomenon in pregnancy. WCH must be ruled out prior to starting these patients on anti-hypertensive medications.